Impacts of dietary Saccharomyces cerevisiae fermentation derived postbiotic on growth performance and health status of Pacific white shrimp - Elangovan Prabu; Nathan Felix; Victor L. Nsereko; Jarin Sawanboonchun; Arumugam Uma; Govindharaj Sathishkumar; Pushparaj Chidambaram; Thangaraju Thiruvasagam; Krishnan Ravaneswaran (Scientific Reports)
Abstract A 60-day feeding experiment was carried out to assess the impacts of dietary Saccharomyces cerevisiae fermentation-derived postbiotic (SCFP) (DVAQUA) on growth performance, nutrient utilization, whole-body proximate composition, digestive and antioxidant enzyme activities, and disease resistance against Vibrio parahaemolyticus in Pacific white shrimp (Penaeus vannamei). Four isonitrogenous, isolipidic, and isocaloric diets were formulated to contain SCFP at 0% (control), 0.25%, 0.35%, and 0.45% of diet. Eight hundred juvenile shrimp (Initial mean weight: 1.54 ± 0.04 g) were randomly allocated into 16 experimental tanks (500 L per tank) of four replicates (n = 4) per treatment (50 shrimp per replicate). The shrimp were fed the experimental diets four times daily at 06.00, 10.00, 14.00, and 18.00 h, for a period of 60 days. At the conclusion of the feeding trial, SCFP supplemented diets enhanced the growth performance and nutrient utilization of P. vannamei. Among the dietary groups, shrimp fed SCFP 0.35 diet had significantly (p < 0.05) higher weight gain, average daily growth, specific growth rate, protein efficiency ratio, and lipid efficiency ratio compared to shrimp fed other experimental diets. Whole-body proximate composition of P. vannamei was not significantly influenced by the dietary SCFP supplementation. Significantly (p < 0.05) protease activity increased in the intestine, while amylase and protease activities significantly increased in the hepatopancreas of shrimp fed SCFP 0.35 diet compared to the control. However, antioxidant enzyme (SOD, CAT, and GPx) activities of shrimp intestine and hepatopancreas were not significantly changed by the dietary supplementation of SCFP. Moreover, shrimp fed the diets containing graded levels of SCFP enhanced disease resistance against V. parahaemolyticus. Significantly lower cumulative mortality during the shrimp challenge test with V. parahaemolyticus was observed in shrimp fed SCFP 0.35 and SCFP 0.45 diets compared to control diet. Overall, the present study indicated that dietary supplementation of SCFP at 0.35% of diet could improve growth performance and nutrient utilization, enhance innate immunity, and strengthen resistance against V. parahaemolyticus in P. vannamei. By improving disease resistance and gut health, SCFP could help minimize the need for antibiotics, potentially reducing the chances of antimicrobial resistance development and contributing to more sustainable and eco-friendly shrimp farming practices.